The impact of board director oversight characteristics on corporate tax agressiveness: An empirical analysis - Richardson, G.; Taylor, Grantley; Lanis, R. (Elsevier, 2013)
This paper examines the impact of board of director oversight characteristics on corporate tax aggressiveness. Based on a 812 firm year dataset of 203 publicly-listed Australian firms over the 2006–2009 period, our regression results show that if a firm has established an effective risk management system and internal controls, engages a big-4 auditor, its external auditor’s services involve proportionally fewer non-audit services than audit services and the more independent is its internal audit committee, it is less likely to be tax aggressive. Our additional regression results also indicate that the interaction effect between board of director composition (i.e., a higher ratio of independent directors on the board) and the establishment of an effective risk management system and internal controls jointly reduce tax aggressiveness.